Global drivers of change across tropical savannah ecosystems and insights into their management and conservation. (December 2022) - Williams, Brooke A.; Watson, James E.M.; Beyer, Hawthorne L.; Grantham, Hedley S.; Simmonds, Jeremy S.; Alvarez, Silvia J.; Venter, Oscar; Strassburg, Bernardo B.N.; Runting, Rebecca K.
Abstract: All tropical savannahs are experiencing extensive transformation and degradation, yet conservation strategies do not adequately address threats to savannahs. Here, using a recently published ecosystem intactness metric, we assess the current condition of tropical savannahs across Earth, finding that <3 % remain highly intact. Moreover, their overall levels of protection are low, and of the protected savannahs, just 4 % can be considered highly intact while the majority (>60 %) are in poor condition. In order to address the clear mismatch between the decline in tropical savannah ecosystems' condition and the response to manage and conserve them, we reviewed the current drivers that lead to tropical savannah degradation and identified conservation approaches being used to address them. Many successful conservation approaches address multiple drivers of change but are applied across small areas. We argue these approaches have the potential to be up-scaled through integrated land-use planning. Highlights: Most tropical savannah ecoregions are now very degraded, with <3 % globally remaining highly intact. Savannahs face multiple interacting threats including development, invasive species, and climate change. The conservation response is not currently sufficient to address the scale of these threats. We link these threatening processes with conservation approaches that address them. We argue that these successful conservation approaches can be more broadly implemented through integrated systematic planning.